Anton Nikitich Yasinsky and the formation of the Belarusian Medieval studies in the 1920s - Maliugin, Oleg I. (Journal of the Belarusian State University. History, 2021)
The article is devoted to the study of the scientific and pedagogical activities of the famous Slavist A. N. Yasinsky in the last – Moscow-Minsk – period of his life based on the materials of the Belarusian archives. Revolutionary events of 1917–1921 forced him, like many other representatives of the capital’s intelligentsia, to look for work in new provincial universities. Since 1922 he has been teaching at the Belarusian State University, becoming one of the founders of Belarusian Medieval and Slavic studies. In 1928 he was elected an academician of the newly created Belarusian Academy of Sciences, where he continued his studies of both the Czech Middle Ages and the history of Belarus in the Middle Ages. However, external circumstances did not allow A. N. Yasinsky to create his own scientific school in Belarus, and his research of the 1920’s remained little known to specialists.